The effectiveness of educational interventions in the community that aim to improve informal carers knowledge of dementia anatomy, physiology, progression, and impact on behavior: a systematic review - Bushell, Dayna; Jones, Cindy; Moro, Christian (Frontiers in Dementia, 2023)
Dementia education is a vital component of dementia care and management for patients and their informal carers and family. To fully understand dementia, some knowledge of the anatomy and physiology of the brain may be necessary and would help informal carers understand behaviors of dementia to help cope with care provision. This integrative review aims to identify, appraise, and assess whether dementia education resources include information detailing the anatomy of the brain and its relationship with dementia and whether this information improves knowledge. (PROSPERO Registration Number: CRD42022320530). Literature published from 2012 until May 4, 2022 was searched in eight databases with six articles meeting the inclusion criteria. Using the Mixed Methods Appraisal Tool (2018) methodological quality varied across studies. There are limited educational interventions which incorporate information on the anatomy and the physiology of the brain. None of the interventions focused solely on providing neurological education; however, all contained at least some content that addressed this, as per inclusion criteria. In most cases, the educational interventions were well-received and delivered, which did not differ, whether they were delivered in person or virtually. The majority of the studies reported an increase in dementia knowledge (measured pre-post or perceived) following the intervention. Educational interventions on brain anatomy and physiology remain limited, and if included, are often not the focus, and as such more rigorous study is required to investigate the effect of educational interventions on dementia knowledge and their role in dementia care.